2006
DOI: 10.1017/s0012162206000211
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival for a cohort of adults with cerebral palsy

Abstract: The aim of this study was to investigate long-term survival and examine causes of death in adult patients with cerebral palsy (CP). A 1940-1950 birth cohort based on paediatric case referral allows for long-term survival follow-up. Survival is analyzed by birth characteristics and severity of disability from age 20 years (and age 2y for a subset of the data). Survival outcome compared with that expected in the general population based on English life tables. The main cohort consisted of 341 individuals, with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 17 publications
1
122
0
2
Order By: Relevance
“…Survival analyses have shown that each of the domains of QoL primarily affected by CP (ambulation, manual dexterity, cognitive ability, hearing, and vision) possesses similar predictive power with regard to mortality; 16,17 however, GMFCS scores for ambulatory disability are the most common within the survival and QoL literature. We assumed that following the onset of CP, 22.5, 12.5, 18, 25, and 22% would experience ambulatory disability (GMFCS levels 1-5, respectively), as demonstrated by Young et al 18 As long-term QoL data were unavailable for those with CP, we extrapolated point estimates of QoL for those with differing extents of CP-related disability (GMFCS 1-5), 19 in order to represent the QoL experienced by those with CP over their entire lifetimes, as shown in Table 1.…”
Section: Base Casementioning
confidence: 99%
“…Survival analyses have shown that each of the domains of QoL primarily affected by CP (ambulation, manual dexterity, cognitive ability, hearing, and vision) possesses similar predictive power with regard to mortality; 16,17 however, GMFCS scores for ambulatory disability are the most common within the survival and QoL literature. We assumed that following the onset of CP, 22.5, 12.5, 18, 25, and 22% would experience ambulatory disability (GMFCS levels 1-5, respectively), as demonstrated by Young et al 18 As long-term QoL data were unavailable for those with CP, we extrapolated point estimates of QoL for those with differing extents of CP-related disability (GMFCS 1-5), 19 in order to represent the QoL experienced by those with CP over their entire lifetimes, as shown in Table 1.…”
Section: Base Casementioning
confidence: 99%
“…Aproximadamente 87% das pessoas com PC sobrevivem até os 30 anos 21 e quase 85% dos que passam dos 20 anos sobrevivem até os 50 anos 22 . Diversos fatores influenciam a sobrevida, como o tipo de PC (por exemplo, a quadriplegia espástica tem o pior prognóstico), presença ou não de epilepsia e deficiência mental grave 21 .…”
Section: Prognóstico Da Pc Expectativa De Vidaunclassified
“…Furthermore, this disability could be accompanied by mental retardation because of reduced oxygen and also further decrease of supply to neural pathways and neuronal structure (7). The fundamental treatment of CP is the individualized multidisciplinary approach (8). A large part of physical disabilities can be improved by rehabilitation therapy.…”
Section: Introductionmentioning
confidence: 99%